(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
According to classic models, intermediary theories are based on transaction costs andasymmetric knowledge. Financial institutions, insurance companies, and the monies they provide tobusinesses are all part of the scope of this system. However, significant adjustments have been madeduring the last few decades. Despite decreased transaction costs and less asymmetric knowledge,intermediation has expanded. New financial futures and options markets are mostly for intermediaries, notindividuals or businesses. The changes we’ve seen thus far cannot be explained by conventional wisdom.We analyze the role of intermediation in this new risk trading and participation cost context.